Construction of perfectly continuous records of physical properties for dark-light sediment sequences collected from the Japan Sea during Integrated Ocean Drilling Program Expedition 346 and their potential utilities as paleoceanographic studies - Tomohisa Irino; Ryuji Tada; Ken Ikehara; Takuya Sagawa; Akinori Karasuda; Shunsuke Kurokawa; Arisa Seki; Song Lu (Progress in Earth and Planetary Science, 2018)
Abstract Establishment of sedimentary sequence is essential for the interpretation of the sedimentary records. Integrated Ocean Drilling Program (IODP) Expedition (Exp.) 346 drilled high-quality sediment archives with more than three holes each at nine sites that enable us to establish continuous sedimentary sequences through splicing technique. After extensive efforts to replace the disturbed, missed, or duplicated intervals found in spliced sediment sequences constructed onboard during IODP Exp. 346 to the corresponding undisturbed intervals, nearly perfectly continuous sediment columns and physical property records for the Pleistocene intervals of Sites U1422-U1427 and U1430 collected from the Japan Sea have been established. Same kind of efforts to correct the shipboard splices were also achieved for Plio-Miocene intervals at Sites U1425 and U1430. The continuous records established for these sites will allow a much more detailed understanding of the long-term variability in East Asian paleoclimate and North Pacific oceanography.